Межгодовая изменчивость структуры вод юго-восточной части тропиков Тихого океана в связи с событиями Эль-Ниньо - Скрипалева, Е.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The interannual variability of the water structure and large-scale fronts due to El-Ni˜no events in the southeast Paciﬁc Tropical zone is investigated with the use of the sea surface temperature (SST) satellite observations during 1985–2002. The signiﬁcant correlation between indices of atmospheric circulation SOI, anomalies of the areas of cold and warm waters in the Peruvian upwelling region and the equatorial zone and front’s characteristics, is found. It is shown that interannual variations during El-Ni˜no events are equal to 1 ◦ С/54 km for front’s intensity, 300–400 km for the spatial displacement, and 6 ◦ С for front’s temperature.